2002
DOI: 10.1128/cmr.15.2.167-193.2002
|View full text |Cite
|
Sign up to set email alerts
|

Biofilms: Survival Mechanisms of Clinically Relevant Microorganisms

Abstract: Though biofilms were first described by Antonie van Leeuwenhoek, the theory describing the biofilm process was not developed until 1978. We now understand that biofilms are universal, occurring in aquatic and industrial water systems as well as a large number of environments and medical devices relevant for public health. Using tools such as the scanning electron microscope and, more recently, the confocal laser scanning microscope, biofilm researchers now understand that biofilms are not unstructured, homogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

62
4,262
7
224

Year Published

2006
2006
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 5,548 publications
(4,555 citation statements)
references
References 196 publications
(162 reference statements)
62
4,262
7
224
Order By: Relevance
“…Biofilms are aggregates of microorganisms in which cells adhere to each other on the surface of living or nonliving substrates. The bacteria in biofilms are known to be 1,000 times more resistant to antibiotics than the floating form of bacteria [2]. After forming biofilms, bacteria penetrate host defenses, thus decreasing antibiotic susceptibility, and releases floating bacteria to new sites [3].…”
Section: Introductionmentioning
confidence: 99%
“…Biofilms are aggregates of microorganisms in which cells adhere to each other on the surface of living or nonliving substrates. The bacteria in biofilms are known to be 1,000 times more resistant to antibiotics than the floating form of bacteria [2]. After forming biofilms, bacteria penetrate host defenses, thus decreasing antibiotic susceptibility, and releases floating bacteria to new sites [3].…”
Section: Introductionmentioning
confidence: 99%
“…Primary and nosocomial infections are not easily prevented or eradicated in the presence of foreign bodies and a poor vascular supply. The presence of graft material and fixation devices provides excellent surfaces for bacterial biofilm formation that are less susceptible to antibiotics and host immune defenses [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Biofilms can be defined as microbial cells attached to a surface and organised into structured communities embedded within a matrix of extracellular material that has been produced by the biofilm cells. 36 Bacterial dental plaque is perhaps the most widely studied biofilm due to its association with caries and periodontal disease and there is increasing interest in the nature of biofilms formed by Candida spp. 37 It is widely recognised that both the biofilm structure and the phenotype of cells within a biofilm can afford protection against both host defence processes and administered antimicrobial agents.…”
Section: Discussionmentioning
confidence: 99%
“…37 It is widely recognised that both the biofilm structure and the phenotype of cells within a biofilm can afford protection against both host defence processes and administered antimicrobial agents. 36,38 Enhanced resistance of a biofilm to an antimicrobial has been related to failure of the agent to diffuse the biofilm, sequestering of the agent within the biofilm matrix, and the presence of persister cells within the biofilm that have a low activity status that promotes their survival in the presence of an antimicrobial. Studies have shown that antimicrobial activity is elevated up to 500-fold in biofilms when compared with equivalent planktonic studies.…”
Section: Discussionmentioning
confidence: 99%